Experimental Study on Surface Integrity of Titanium Alloy Ti6Al4V by Ball End Milling - Kaway, Pun Krishna; Zhang, Xueping (Journal of the Institute of Engineering, 2018)
Titanium alloy, Ti6Al4V, has been widely used in aerospace, automotive, biomedical, and chemical industries due to its exceptional strength to weight ratio, high temperature performance, and corrosion resistance. However, machinability of Ti6Al4V is poor due to high strength at elevated temperatures, low modulus, and low thermal conductivity. Poor machinability of Ti6Al4V deteriorates the surface integrity of the machined surface. Poor surface integrity causes high machining cost, surface defects, initiate cracks, and premature failure of the machined surface. Thus, it is indispensable to obtain better surface integrity when machining titanium alloy Ti6Al4V. Cutting parameters such as cutting speed, feed rate, and depth of cut have significant effect on the surface integrity when machining titanium alloy Ti6Al4V. Hence, this study investigates surface integrity of Ti6Al4V by ball end milling at different cutting speeds, feed rates, and depth of cuts. Microstructure of subsurface is studied at different cutting speeds, feed rates, and depth of cuts. The results show that the depth of deformation of subsurface increases with increase in the cutting speed, feed rate, and depth of cut. Journal of the Institute of Engineering, 2018, 14(1): 115-121